Audit of Vascular Access Surgery in A Tertiary Care Hospital - Arif, Anum; Haadi, Osama; Bhatti, Ahsin Manzoor; Ali Inam, Syed Hashim; Baig, Zahid Farooq; Cheema, Ali Hamza (Pakistan Armed Forces Medical Journal, 2022)
Objective: to analyze the outcomes of arteriovenous fistula (AVF) constructed in our setup.Study Design: Retrospective observational study.Place and Duration of Study: Combined Military Hospital, Lahore, from Mar 2019 to Mar 2020.Methodology: Our study included all the patients who had their arteriovenous fistula (AVF) made during the study period. Data was collected via telephone calls, to inquire about the status of AV fistula after one year of AV fistula construction surgery.Results: Out of 130 study participants, 97 were successfully contacted. Mean age of patients was 54 .39 ± 12.75 years. Majority were male patients (71.1%) and had their first dialysis via temporary dialysis access catheter. Most of the patients (74.7%) had functional AVF. 35 (36.1%) patients were not alive at the time of contact. In 9 (9.2%) patients, AV fistula failed with the most common cause being thrombosis (77.7%).Conclusion: Current study is one of the pioneer in Pakistan where we have started to audit our performance as the dedicated access surgeons. It is high time for us to evaluate our performance so that better outcome can be offered to the dialysis dependent patients.